Stock markets, banks, and economic development: Theory and evidence - Thorsten Beck (EIB Papers, 2003)
This paper discusses the different functions that capital markets and banks have in economic development, and it reviews the debate about marketbased vs. bank-based financial systems. Using data for a sample of 40 countries over the period 1975-98, the paper then shows that variation in both banking sector and stock market development can explain variation in economic growth, but the degree to which a financial system is market- or bank-based cannot explain economic development across countries. This is consistent with the financial services view, which focuses on the services provided rather than the providers of services and which emphasises complementarities between markets and intermediaries.
Keywords: 330; Aktienmarkt; Bank; Unternehmensentwicklung; Wirtschaftswachstum; Schätzung; Panel; Welt